THE IMPORTANCE AND BENEFITS OF STEAM TECHNOLOGIES TODAY (International journal of artificial intelligence, 2025)
This article discusses the current importance of STEAM technologies, their capabilities and achievements, and their advantages in the education system, as well as the activities of development centers in MTTs. This article can be used by students, free and independent researchers, and educators.